The beast from the East : a goosebumps book. - "Stine. R.L" (Scholastic: New York, 2005)
Ginger and her twin brothers Nat and Pat get lost in a strange part of the woods and find themselves playing a life-or-death game of tag with a group of blue, furry beasts
Keywords: Horror fiction